Mental ability test for Philippine secondary schools - Padilla, Leila Madeline 1932- (1954)
A test which is reliable and valid for the purpose of determining the intelligence and mental ability of Filipino students of the high school level was constructed. The study also aimed to construct norms for this test in all levels of the high school - for the first year, second year, third year, and fourth year so that it will be applicable to all years in high school.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Mental tests